Noren discount stores: death of a family business - Goldberg, Steven D (Family Business Review, 1997)
This case is about a family-owned discount store chain that was unable to survive much beyond its founder. It tells the story of a first-generation American family and its struggle to grow and prosper in a family business during the early 1900s. The case takes the reader through the business' growth, maturity, decline, and, ultimately, its demise in 1991, which was brought about by issues such as organizational structure, the role of family in the family business, lack of succession planning, and myopic strategic planning. The author uses fictitious names, dates, and places to protect the surviving family members' privacy, and to ensure confidentiality.
Keywords: dept.mgt

Give your work teams time and training - Cottrill, Melville (Academy of Management Perspectives, 1997)
Keywords: dept.mgt